Structural basis for endotoxin neutralization by the eosinophil cationic protein. (31st October 2016) - Pulido, David; Garcia‐Mayoral, Maria Flor; Moussaoui, Mohammed; Velázquez, Diego; Torrent, Marc; Bruix, Marta; Boix, Ester
Abstract : Acute infection by Gram‐negative pathogens can induce an exacerbated immune response that leads to lethal septic shock syndrome. Bacterial lipopolysaccharide (LPS) is a major pathogen‐associated molecular pattern molecule that can initiate massive and lethal immune system stimulation. Therefore, the development of new and effective LPS‐neutralizing agents is a top priority. The eosinophil cationic protein (ECP) is an antimicrobial protein secreted in response to infection, with a remarkable affinity for LPS. In the present study, we demonstrate that ECP is able to neutralize bacterial LPS and inhibit tumor necrosis factor‐α production in human macrophages. We also characterized ECP neutralizing activity using progressively truncated LPS mutants, and conclude that the polysaccharide moiety and lipid A portions are required for LPS‐mediated neutralization. In addition, we mapped the structural determinants required for the ECP–LPS interaction by nuclear magnetic resonance. Our results show that ECP is able to neutralize LPS and therefore opens a new route for developing novel therapeutic agents based on the ECP structural scaffolding. Abstract : Acute infection by Gram‐negative pathogens can end in lethal lipopolysaccharide (LPS) septic shock syndrome. In this work we demonstrate that the eosinophil cationic protein (ECP) is able to neutralize LPS action through the inhibition of tumor necrosis factor‐α (TNF‐α) release. Additionally, we have mapped the structural determinants required for the ECP‐LPS interaction by nuclear magnetic resonance (NMR). These results contribute to the development of new therapeutic agents.